2020
DOI: 10.18632/aging.202316
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and environmental factors have opposite AhR-dependent effects on C. elegans healthspan

Abstract: Genetic, dietary, and environmental factors concurrently shape the aging process. The aryl hydrocarbon receptor (AhR) was discovered as a dioxin-binding transcription factor involved in the metabolism of different environmental toxicants in vertebrates. Since then, the variety of pathophysiological processes regulated by the AhR has grown, ranging from immune response, metabolic pathways, and aging. Many modulators of AhR activity may impact on aging and age-associated pathologies, but, whether their effects a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 89 publications
4
27
0
Order By: Relevance
“…cyp-13A5 and cyp-13A8, cyp-42A1) were increased by curcumin only in the absence of ahr-1 (Fig S1). These data, along with other works (Brinkmann et al, 2020b, Jones et al, 2013, suggest that cyps are likely not the major targets of CeAhR. This is also supported by our transcriptomic analysis in wild-type and ahr-1 mutants.…”
Section: Ugt-45 Mediates the Anti-aging Effects Of Curcumin And Ahr-1...supporting
confidence: 90%
See 3 more Smart Citations
“…cyp-13A5 and cyp-13A8, cyp-42A1) were increased by curcumin only in the absence of ahr-1 (Fig S1). These data, along with other works (Brinkmann et al, 2020b, Jones et al, 2013, suggest that cyps are likely not the major targets of CeAhR. This is also supported by our transcriptomic analysis in wild-type and ahr-1 mutants.…”
Section: Ugt-45 Mediates the Anti-aging Effects Of Curcumin And Ahr-1...supporting
confidence: 90%
“…We used the following C. elegans strains: N2 [wild-type], CZ2485 [ahr-1(ju145)], NV38b Growth Media (NGM) plates and fed with E. coli OP50 according to methods described in (Brinkmann et al, 2020b). For the experiments, worms were synchronized on plates supplemented with E. coli HT115(DE3) on plates supplemented with 1 mM IPTG.…”
Section: Elegans C Elegans Strains and Cultivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, similarities between C. elegans pharyngeal muscle and the vertebrate heart in terms of anatomic development and physiology have been described, which suggest convergent evolution between two autonomous muscular pumps with similar biological roles [29]. Strikingly, automatic measurement through a microfluidic device [30] revealed that nuo-5 and lpd-5 RNAi-treated animals have an abnormal electropharyngeogram (EPG) with significantly decreased pump frequency ( Fig 2C ) and increased average inter-pump interval (IPI) as well as R o E ratio when compared to control nematodes ( Fig S2G,H ).…”
Section: Resultsmentioning
confidence: 99%